2001
DOI: 10.1007/s004210100422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise intensity on the changes in alveolar slopes of carbon dioxide and oxygen expiratory profiles in humans

Abstract: The slope of the expired alveolar partial pressure of carbon dioxide pro®le increases during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In the absence of a true criterion test for exercise ventilatory inefficiency, we relied on a cluster of variables that are indirect markers of pulmonary gas-exchange disturbances. In this context, exercise induced elevations in PETCO 2 reflect either true carbon dioxide retention or delayed lung emptying in COPD [37,38]. Considering that PETCO 2 grossly underestimates alveolar carbon dioxide tension in these patients [36], our assumptions, which are increases in PETCO 2 indicate more severe gas exchange disturbances in COPD, still hold true.…”
Section: Figurementioning
confidence: 72%
“…In the absence of a true criterion test for exercise ventilatory inefficiency, we relied on a cluster of variables that are indirect markers of pulmonary gas-exchange disturbances. In this context, exercise induced elevations in PETCO 2 reflect either true carbon dioxide retention or delayed lung emptying in COPD [37,38]. Considering that PETCO 2 grossly underestimates alveolar carbon dioxide tension in these patients [36], our assumptions, which are increases in PETCO 2 indicate more severe gas exchange disturbances in COPD, still hold true.…”
Section: Figurementioning
confidence: 72%
“…Second, Whipp et al (43) pointed out that Grønlund's approach may provide a different breath duration under specific conditions, such as during the transition from rest to exercise, compared with that of the conventional flow-based approach. Since the slope of the alveolar partial pressure of expired O 2 (and CO 2 ) increase at the onset of exercise and during continued exercise (38), a particular intra-breath 𝐹 reference value at t1 might be reached earlier during the expiration phase at t2, which in turn would result in a shorter estimated breath duration, and differentially alter the durations of inspiratory and/or expiratory time (such as in t I /t E or t I/ t TOT ), than with the conventional approach (43). The same concern applies to the CF algorithm ( 16), although specific aspects of this algorithm may help mitigate this concern (see below) (39,41).…”
Section: Limitations Methodological Considerations and Future Directionsmentioning
confidence: 99%
“…Although unlikely, a given reference value at t1 may not be attained at t2 over a long series of breaths, which would result in losing the breath considered (Figure 4B) (see Capelli et al for further details) (10). This may occur during hyperventilation, where tachypnea increases the slope of the alveolar partial pressure of expired O 2 (and CO 2 ) (38) (see below for further details).…”
Section: *Figure 3 Near Here*mentioning
confidence: 99%
“…The beta angle measures close to 90° (Smalhout andKalenda et al 1981, Bhavani-Shankar et al 1995). Many studies have shown phase III (alveolar plateau) to hold some discrimination ability for asthmatic and non-asthmatic patients (Gravenstein 2004), and to increase during exercise (Steinacker et al 2001). Yaron et al proposed a method to calculate the slope of the alveolar plateau, whose units are mmHg s −1 (Yaron et al 1996).…”
Section: Capnogram Shape As Physiological State Indicatorsmentioning
confidence: 99%